A Literature Review of Distribution Solving Problems by Various Transportation Methods - Nursafwah; Matondang, Nazaruddin; Ishak, Aulia (TALENTA Publisher, 2023)
The aim of this study to review the limited survey of a systematic various existing transportation problems and the application developed by different researchers and applied in some case studies. The methodology applied in this paper through various research papers that available at Google Scholar, Science direct, Elsevier, IOP and another publisher from 2014-2022 (twenty-four international researches). The main purpose of this review paper is to discuss, analyze and the existing forms of various types of transportation problems and their systematic development, Findings show that in addition to the MODI and VAM methods, other methods have also emerged to solve the transportation problem. One of them is Improve VAM (IVAM) that built by Nahar et.al (2018). IVDM on transportation or delivery strategy. Further, this paper concludes that mathematical models and algorithm method of transportation derivatives/techniques of MODI and VAM are most used to optimize single or multipurpose parameters such as distribution cost, profit earned, total transportation time etc.